Determining Factors of Dividend Payout Ratio in The Top Five Banking Companies on The Indonesian Stock Exchange - Toni Prihandoko; Fajriyatul Abadiyah (Petra International Journal of Business Studies, 2024)
One manifestation of investing is getting dividends or giving the company free bonuses, which are distributed to investors based on excess profits generated in a certain period. This research seeks to examine the influence of profitability and capital structure on the dividend payout ratio, which includes indicators of net profit margin (NPM), return on assets (ROA), return on investment (ROI), and debt-to-equity ratio (DER). Panel data regression analysis is used in this research to answer the problem formulation with an observation period from 2018-2022. The research results show that net profit margin and debt-to-equity ratio have a negative and significant effect on the dividend payout ratio, while return on assets and return on investment do not have a significant effect on the dividend payout ratio of the top five banking companies listed on the Indonesia Stock Exchange.